2015
DOI: 10.13188/2378-1343.1000007
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Vasodilatation Induced by Rokumigan, Hachimijiogan, and Goshajinkigan in the Rat Aorta

Abstract: Rokumigan, hachimijiogan, and goshajinkigan are traditional Japanese Kampo formulations with similar components and consequently similar clinical indications. These formulations are considered useful for the management of edema, water disturbances, dry skin, dry mouth, and abnormal urination. Rokumigan is composed of six types of crude herbal drugs, hachimijiogan comprises rokumigan and two crude drugs, and goshajinkigan includes hachimijiogan and two other crude drugs. In this study, we compared the vasodilat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 20 publications
(24 reference statements)
1
8
0
Order By: Relevance
“…The exact compositions of crude drugs in three kampo formulations are summarized in Table 1. We have shown the same summary of compositions in previous article entitled "comparative study of vasodilatation induced by rokumigan, hachimijiogan, and goshajinkigan in the Rat aorta" of this journal [2].…”
Section: Introductionsupporting
confidence: 66%
See 3 more Smart Citations
“…The exact compositions of crude drugs in three kampo formulations are summarized in Table 1. We have shown the same summary of compositions in previous article entitled "comparative study of vasodilatation induced by rokumigan, hachimijiogan, and goshajinkigan in the Rat aorta" of this journal [2].…”
Section: Introductionsupporting
confidence: 66%
“…To investigate the endothelium dependency of vasodilatations, L-NAME (100 μM) and endothelium removal were pretreated. In young rats, we have been reported that L-NAME and endothelium removal attenuated kampo formulations-induced vasodilatations in previous reports [2]. However, in aged rats, L-NAME and endothelium removal did not attenuate rokumigan-induced vasodilatations at 0.03 -1.0 mg/mL (Table 2).…”
Section: Age-dependent Modulation Of Endothelium-dependent Vasodilatations Induced By Rokumigan Hachimijiogan and Goshajinkiganmentioning
confidence: 64%
See 2 more Smart Citations
“…Moreover, Nishida et al . demonstrated the vasodilatory effect of GJG on norepinephrine‐induced vasoconstriction in a concentration‐dependent manner in rat aorta through NO production [11]. These results strongly suggest that GJG could cause vasodilation via NO production in diabetic mice.…”
Section: Introductionmentioning
confidence: 88%